CONTAMINANTS AND CLEAN TECHNOLOGIES - Chowdhary, Pankaj; Raj, Abhay ([S.l.] : CRC PRESS, 2020)
Contaminants and Clean Technologies provides valuable information on environmental contaminants such as industrial pollutants, micropollutants, pesticides, endocrine disruptors, pharmaceuticals, toxins, and hormones. It focuses on the various types of environmental contaminants discharged from various sources; their toxicological effects in environments, humans, animals, and plants; and their removal methods. It also covers, comprehensively, information on the contaminants released by various industries and agricultural practices, which cause severe threats to the environment. Features of the book: Elucidates systematic information on various types of environmental contaminants, and their fate and consequences Discusses contaminants such as endocrine disruptors, pharmaceutical waste, andpersonal care products Provides an overview of physicochemical and biological treatment technologies for sustainable development Details recent research finding in the area of environmental contaminants and their future challenges
Chapter 1 Emerging Environmental Contaminants: Sources, Consequences, and Future Challenges Pankaj Chowdhary, Vishvas Hare, Anil K. Singh, Preeti Chaturvedi, and Soumya Pandit Chapter 2 Biological Treatment of Sulfate-Rich Wastewater Ariovaldo Jose da Silva, Bruna Sampaio de Mello, and Arnaldo Sarti Chapter 3 Wetland Plants: Recent Advances in Removal of Pollutants from Contaminated Site Poonam and Mahesh Kumar Chapter 4 Toxic Contaminants in Herbal Medicines Bhanu Kumar and Subir Kumar Bose Chapter 5 Toxicity Evaluation of Paper Mill Pollutants Using In Silico Toxicology Approach for Environment Safety Anil Kumar Singh, Pankaj Chowdhary, and Abhay Raj Chapter 6 Effect of Arsenic on Human Health and Its Removal through Physiochemical Techniques Vishvas Hare, Pankaj Chowdhary, Siddarth Boudh, Anil Kumar Singh, Sujata Mani, and Amit Kumar Chapter 7 Synthesis, Characterization, and Remediation Application of Iron Oxide Nanoparticles Sandhya Singh, Gaurav Hitkari, and Gulam Abbas Chapter 8 Dyes: Industrial Applications and Toxicity Profile Sujata Mani and Pankaj Chowdhary Chapter 9 Importance of Bacterial Biofilm in Bioremediation Rishi Pramod Babu, Soumya Pandit , Namita Khanna, Pankaj Chowdhary, Abhilasha Singh Mathuriya, and Elvis Fosso-Kankeu Chapter 10 Arsenic: Threat to Water as Well as Soil Kiran Gupta, Alka Srivastava, and Amit Kumar Chapter 11 Aquatic Plants as Effective Phytoremediators of Heavy Metals Sandip Singh Bhatti, Sartaj Ahmad Bhat, and Jaswinder Singh Chapter 12 Biodiesel as a Renewable Energy Source: An Alternative to Conventional Fuel Siddharth Boudh, Surabhi Zainith, Pankaj Chowdhary, and Sandhya Mishra Chapter 13 Phytoremediation of Heavy Metals-Polluted Soil Amjad Ali, Di Guo, Amanullah Mahar, Fazli Wahid, Parimala Gnana Soundari Arockiam Jeyasundar, Muhammad Azeem, Ronghua Li, and Zengqiang Zhang Chapter 14 Advanced Nanofiltration Membranes for Wastewater Treatment Oluranti Agboola, Samuel E. Sanni, Rotimi Sadiku, Patricia Popoola, and Victoria Oluwaseun Fasiku Chapter 15 Vermicomposting: A Sustainable Approach for Recycling of Excess Sludge Guangyu Cui, Sartaj Ahmad Bhat, Shuailei Li, Wenjiao Li, and Fusheng Li Chapter 16 Food Industries and Recycled Water: Current Strategies and New Opportunities Salvatore Parisi, Rajeev K. Singla, Arun Garg, and Ashok K. Dubey Chapter 17 Application of Biosorption Technique for Removal of Heavy Metals Present in Water or Wastewater Poonam and Narendra Kumar Chapter 18 Microalgae as Nature's Doctor: An Aid in Saving Environment Trashi Singh, Tanim Arpit Singh, Payal Basu, Rani Durgavati Vishwavidhyalaya , Siddharth Boudh, and Pradeep Shukla Chapter 19 Smart Waste Management and Energy Extraction from Waste in Indian Smart Cities -- A Review Shailendra Kumar Yadav, Kanagaraj Rajagopal, A.K. Priya, and Gyan Deep Sharma
OCLC-licensed vendor bibliographic record.
Keywords: Pollutants; Environmental toxicology; Pollution prevention; LAW / Environmental; SCIENCE / Environmental Science; SCIENCE / Life Sciences / General